PARP1 inhibitors in breast cancer therapy. Mechanism of action and clinical use - D. S. Dolgasheva; A. M. Pevzner; M. K. Ibragimova; N. V. Litvyakov; M. M. Tsyganov (Опухоли женской репродуктивной системы, 2020)
It is known that currently PARP inhibitors are actively used in the treatment of tumors of the female reproductive system. A large number of studies have been presented demonstrating the effectiveness of PARP inhibitors in the treatment of BRCA-associated ovarian cancer. It was found that mutations in the BRCA1 and BRCA2 genes are also characteristic of breast cancer (BC). However, PARP inhibitors are rarely used in clinical practice in the treatment of BC. So far, only olaparib has become the first PARP inhibitor approved for the treatment of metastatic BC. This review presents data over the past ten years showing the high efficiency of PARP inhibitors in the treatment of malignant neoplasms of the mammary gland. In 7 of 28 studies analyzed, positive results were achieved with combined treatment with chemotherapeutic drugs and PARP inhibitors. So, for example, in two studies in the treatment of BRCA-associated BC, the response to treatment in patients was 72.5–73.2 %. Thus, PARP inhibitors are of great interest and are of practical value in the treatment of patients with BC.